Inter-provenance variability and phenotypic plasticity of wood and leaf traits related to hydraulic safety and efficiency in seven European beech (Fagus sylvatica L.) provenances differing in yield - Daniel Kurjak; Peter Petrík; Alena Sliacka Konôpková; Roman M. Link; Dušan Gömöry; Peter Hajek; Mirko Liesebach; Christoph Leuschner; Bernhard Schuldt (Annals of Forest Science, 2024)
Abstract Key message Seven European beech provenances differing largely in growth performance were grown at two common garden sites in Germany and Slovakia. The intra-specific variability of most traits was explained more by phenotypic plasticity than inter-provenance variability, and efficiency-related traits showed a higher phenotypic plasticity than safety-related traits. Context To maintain climate-resilient future forests, replicated common-garden experiments are suited for developing assisted migration strategies for key tree species. Aims We analysed the magnitude of inter-provenance variability and phenotypic plasticity for 12 functional traits of European beech (Fagus sylvatica L.) and analysed whether the climate at the place of origin left an imprint. Moreover, we asked whether growth is unrelated to xylem safety and to what extent the foliar, xylem and growth-related traits are coordinated. Methods Terminal branches were collected from 19-year-old and 22-year-old trees of seven European beech provenances planted at two common garden sites in Germany and Slovakia, respectively. Three hydraulic, three wood anatomical and four foliar traits were measured and related to two growth-related variables. Results At the two sites, the same pair of provenances showed the highest and lowest growth. Nevertheless, a high degree of phenotypic plasticity was observed, as all traits differed significantly between sites after accounting for provenance effects, with hydraulic safety-related traits showing the lowest and efficiency-related traits the highest plasticity. There was no evidence for inter-provenance variability in xylem embolism resistance (P 50) or the foliar carbon isotope signature (δ13C), a proxy for intrinsic water use efficiency (iWUE), and both were unrelated to growth. P 50 was positively correlated with the lumen-to-sapwood area ratio and vessel density. Conclusions Because of the lacking trade-off between embolism resistance and growth, highly productive provenances can be selected without reducing the drought tolerance of the branch xylem. However, as xylem safety is only one element of a trees’ drought response, it may be beneficial to select provenances with other more conservative drought adaptations such as smaller vessel lumen areas for increasing xylem safety and small supported total leaf areas for reduction of total transpiration.